The relationship of pharmaceutical services toward the use of herbal medicine : Indonesian case - Putu Eka Arimbawa; Dewi Puspita Apsari; I Gusti Ngurah Agung Windra Wartana Putra; Muhammad Iqbal Fasa (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2020)
Pharmaceutical services are services provided by a pharmacist in providing health information including the use of herbal medicines. The purpose of this study was to look at the relationship between pharmaceutical services and the use of herbal medicines in the city of Denpasar. The number of samples used was 97. Data were collected from January to February 2020 in the city of Denpasar using a questionnaire. Data were analyzed using the binary logistic test. The results showed that pharmaceutical services did not have a significant relationship with the use of herbal medicines (P> 0.05). Pharmaceutical services such as completeness of the drug, pharmacist's readiness to assist, and the speed of drug preparation services that are less good can affect the physical, mental, and spiritual aspects of herbal medicine.